2023
DOI: 10.1021/acs.est.2c07441
|View full text |Cite
|
Sign up to set email alerts
|

Persisting Effects in Daphnia magna Following an Acute Exposure to Flowback and Produced Waters from the Montney Formation

Abstract: Hydraulic fracturing extracts oil and gas through the injection of water and proppants into subterranean formations. These injected fluids mix with the host rock formation and return to the surface as a complex wastewater containing salts, metals, and organic compounds, termed flowback and produced water (FPW). Previous research indicates that FPW is toxic to Daphnia magna (D. magna), impairing reproduction, molting, and maturation time; however, recovery from FPW has not been extensively studied. Species unab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…10,11 Further studies have used Daphnia magna, such as those by Boyd et al, who investigated the toxicity of flowback water from the Montney Formation in Canada. 12 Azetsu-Scott et al, using Microtox tests, found that toxicity increased over time following discharge of PW from offshore oil production installations due to the precipitation of heavy metals present in PW. 13 Overall, there is a lack of research on the toxicity of treated PW.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Further studies have used Daphnia magna, such as those by Boyd et al, who investigated the toxicity of flowback water from the Montney Formation in Canada. 12 Azetsu-Scott et al, using Microtox tests, found that toxicity increased over time following discharge of PW from offshore oil production installations due to the precipitation of heavy metals present in PW. 13 Overall, there is a lack of research on the toxicity of treated PW.…”
Section: Introductionmentioning
confidence: 99%
“…Hull et al observed significant cytotoxicity in PW from the Denver-Julesburg basin in Colorado via bioluminescence over a 220-day period . McLaughlin et al studied the acute toxicity on Daphnia magna from a minimally treated PW discharged into a stream used for agriculture and livestock and found several chemicals above their MCL thresholds at the discharge site, including known carcinogens. , Further studies have used Daphnia magna , such as those by Boyd et al, who investigated the toxicity of flowback water from the Montney Formation in Canada . Azetsu-Scott et al, using Microtox tests, found that toxicity increased over time following discharge of PW from offshore oil production installations due to the precipitation of heavy metals present in PW .…”
Section: Introductionmentioning
confidence: 99%
“…Further, the toxicity level of the treated produced water, which indicates potential ecological and health impacts, presents a significant risk but has rarely been discussed in the literature pertaining to produced water treatment. Indeed, the toxic effects of untreated produced water have been demonstrated for various organisms, ,, rendering toxicity a key indicator for ensuring sufficient treatment.…”
Section: Introductionmentioning
confidence: 99%